A genetic exploration of cognitive decline in Alzheimer's disease. (December 2021) - Katzourou, Ioanna; Leonenko, Ganna; Sims, Rebecca; Williams, Julie; Holmans, Peter; Escott‐Price, Valentina; ,; ,
Abstract: Background: The rate of cognitive decline in Alzheimer's disease (AD) has been found to vary widely between individuals, with numerous factors driving this heterogeneity. This study aims to explore the genetic architecture of cognitive decline in AD. Methods: We used a subset of 543 individuals with AD from the GERAD cohort (Harold et al ., 2009) and a subset of 180 individuals with AD from the ADNI dataset (Mueller et al ., 2005) with genetic data and cognitive assessments at multiple timepoints. Firstly, a metric of cognitive decline for each individual was estimated as the random slope from a random effects regression model of Mini Mental State Examination (MMSE) scores. This metric was consequently used to perform genome‐wide association studies of cognitive decline in each dataset, which were then meta‐analysed. Two polygenic risk score (PRS) analyses were performed, one exploring the polygenic heritability of decline in AD and the other examining the shared genetic architecture between decline and AD risk, based on the latest AD GWAS (Kunkle et al ., 2019). Results: Meta‐analysis revealed 8 variants reaching genome‐wide significance. Rate of decline PRS based on summary statistics from the GERAD data was not associated with decline in the ADNI dataset. Finally, AD risk PRS was not associated with rate of decline in either dataset. Conclusions: The lack of association of the AD risk PRS with rate of decline might indicate that the genetic risk for accelerated cognitive decline within AD is separate from the genetic risk for developing AD. The power of this study is limited by the small sample sizes, and replication in a larger dataset is necessary both to validate these findings and uncover additional variants that affect the rate of decline in AD.